Kolaborasi Pembelajaran Problem Posing dan Problem Solving Untuk Meningkatkan Hasil Belajar Siswa SMP Salibutaibin - Fitriya, Lailatul; Siskawati, Fury Styo (FKIP Universitas Islam Jember, 2021)
This study aims to improve student learning outcomes in studying Collaborative Sets of Problem Possing and Problem-Solving learning models using the Scientific Approach. The type of this research used is Classroom Action Assessment (PTK), with research procedures using a cycle model, from the results of the study the percentage of student learning outcomes in cycle I reached 65% and cycle II was 90%, while student activity increased from cycle I to cycle. II, namely 70% to 81% This proves that the level of understanding of students increases with the application of the Collaborative Problem Possing and Problem Solving learning model using the Scientific Approach, so that learning can properly provide an illustration with examples of its basic illustrations.